Low-income rural youth migrating to urban universities in South Africa: opportunities and inequalities. Issue 8 (16th November 2020) - Walker, Melanie; Mathebula, Mikateko
ABSTRACT: In order to understand how students from low-income rural backgrounds in South Africa experience higher education and the opportunities and obstacles they encounter, the paper draws on two waves of interviews with 30 students currently studying at three large urban universities. Using concepts of capabilities and functionings, monetary resources and 'capitals', the paper outlines common factors which shape rural students' well-being and their agency in accessing an urban university. Student voices indicate the particular importance of being able to exercise the functioning of navigating and manoeuvring through unfamiliar and often intimidating institutions. The discussion also indicates that it is the intersection of rurality and low income which shapes, even if it does not over-determine, their lives at university. It is suggested that universities could do more to support these students' well-being, and to recognise the agency and admirable determination which students bring to the challenges they face.